Knowledge of professionals for providing social services for old people - Stojkovska, Daniela (Ревија за социјална политика/Journal of Social Policy, 2020)
Demographic aging, which is increasingly becoming a reality in the Republic of North Macedonia, brings challenges for the development of appropriate social services, according to the needs of the elderly, but also the need to acquire and deepen the knowledge of professionals who provide these services. All this is imposed as a need for one purpose and that is to meet the needs of the elderly. The professional development of social protection professionals in the Republic of North Macedonia is part of a comprehensive process that seeks to follow European trends for continuous professional development. However, the fact that the development of social services for the elderly in North Macedonia follows experiences increased dynamics in recent years, and is expected to develop faster with the reformed social protection system from 2019, imposes the need to study the knowledge whereby professionals enter the provision of social services, as well as the need to expand and deepen them. This paper is aimed at studying the knowledge of professionals who provide social services to the elderly, and the results of quantitative research conducted with professionals, indicate the need to strengthen them during vocational education and the process of continuous professional development.
Keywords: knowledge; professionals; social services; elderly